Pendampingan Belajar Anak Diskalkulia Di Pesantren Nurul Jadid Menggunakan Media Pembelajaran Berbasis Android - Jannatul Hasanah; Siti Fatimatuz Zahroh; Moh. Syadidul Itqan; Mohammad Nur Kholik (J-PEMAS - Jurnal Pengabdian Masyarakat, 2021)
Children who have different conditions from other normal children both in terms of mental, physical, and social characteristics are called children with special needs. A different approach is also needed in Teaching and Learning Activities (TLA) with other normal children, because of the different conditions with other normal children. Using an Android-based learning media device is one of the different approaches as an effective learning strategy for children with special needs to help understand the material presented by the teacher. This community service was carried out at Nurul Jadid Middle School, Paiton District, Probolinggo Regency, for the 2020/2021 Academic Year. applied android applications to help children with special needs learn is the goal of this community service. This community service method is community service development (Research & Development The procedure used in this community service is the ADDIE development model, the development consisting of five stages consisting of Analysis, Design, Development, Implementation, and Evaluation. The results of this community service have applied an android application as an effective learning strategy for children with special needs at the Nurul Jadid Islamic Boarding School.